(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate factors associated with plasma Procalcitonin (PCT) and C-reactive protein (CRP) of inpatients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD) at the National Lung Hospital. Subject and method: A cross-sectional study was conducted on 200 patients diagnosed with AECOPD and admitted to the National Lung Hospital from November 2023 to May 2024. Clinical factors, Anthonisen classification, GOLD 2023 stages, and biomarkers (PCT, CRP, and white blood cell counts) were evaluated. Results: Most patients were male (91.5%) and aged 60-79 (76.9%), with 64.0% having ≥2 hospital admissions/year and 76.0% still smoking. COPD duration of 5-10 years accounted for 49.0%, with an average hospital stay of 13.24 ± 9.08 days. Plasma CRP and PCT levels were highest in Anthonisen I and GOLD 4 at admission and lowest in Anthonisen III and GOLD 1 before discharge (p < 0.01). CRP showed a positive correlation with PCT (r = 0.192, p < 0.01) and white blood cell count (r = 0.210, p < 0.01). Conclusion: CRP and PCT are reliable biomarkers reflecting disease severity and systemic inflammation in AECOPD patients. This study provides essential evidence to support the optimization of diagnosis and management of AECOPD.